Then sings my soul : 150 of the world's greatest hymn stories - Morgan, Robert J., 1952- (Nashville, Tenn. : Thomas Nelson, 2003)
"The author's lifelong interest in hymns led him to discover the richness of the stories behind many of the best-loved hymns. Many of the stories also reflect the impact hymns have had on ordinary people as they read, heard, and sang the great hymns of faith."--Cover.
Does your soul lift in song when you hear the first few bars of a favorite hymn? Robert Morgan's lifelong interest in hymns led him to discover the richness of the stories behind many of the best-loved hymns. Many of the stories also reflect the impact hymns have had on ordinary people as they read, heard, and sang the great hymns of the faith. One of the author's goals in writing these stories is to help people reacquaint themselves with these wonderful, old hymns and the importance of keeping the hymns as a vital and meaningful part of today's church. This book includes 150 devotional-style stories, complete with music and lyrics, and indexes by title, first line, and writer. - Back cover.
The cure for shot nerves -- The Lord bless you and keep you -- Be Thou my vision -- All glory, laud, and honor -- Jesus, the very thought of Thee -- All creatures of our God and King -- The God of Abraham praise -- A mighty fortress is our God -- Now thank we all our God -- The Lord's my Shepherd -- Doxology -- Praise God, from whom all blessings flow -- Sing praise to God who reigns above -- Fairest Lord Jesus -- Praise ye the Lord, the Almighty -- Behold the Savior of mankind -- Behold the glories of the Lamb -- Alas! and did my Savior bleed -- I sing the mighty power of God -- Jesus shall reign -- O God, our help in ages past -- God is the refuge of His saints -- Am I a soldier of the cross? -- An can it be that I should gain? -- O for a thousand tongues to sing -- Hark! The herald angels sing -- Christ the Lord is risen today -- Jesus, lover of my soul -- Hallelujah chorus (from The Messiah) -- Messiah (Handel) -- O come, all ye faithful -- When morning gilds the skies -- Guide me, O Thou great Jehovah -- O happy day, that fixed my choice -- Come, Thou fount of every blessing -- Father, whate'er of earthly bliss -- There is a fountain -- O for a closer walk with God -- God moves in a mysterious way -- Rock of ages -- All hail the power of Jesus' name -- Amazing grace -- Though troubles assail us -- How firm a foundation -- There is a balm in Gilead -- Praise the Savior, ye who know Him! -- The Star-Spangled Banner -- Angels from the realms of glory -- Silent night -- Jesus, I my cross have taken -- In the cross of Christ I glory -- Holy, holy, holy! Lord God Almighty -- My faith looks up to Thee -- Of for a faith that will not shrink -- My country, 'Tis of Thee -- Lead, kindly light -- O worship the King -- The solid rock -- Just as I am -- Nearer, my God, to Thee -- I heard the voice of Jesus say -- Abide with me -- It came upon the midnight clear -- In heavenly love abiding -- Crown Him with many crowns -- Good King Wenceslas -- Still, still with Thee -- What a friend we have in Jesus -- More love to Thee, O Christ -- Stand up, stand up for Jesus -- Eternal Father, strong to save -- Jesus loves me -- I gave my life for thee -- Battle hymn of the republic -- He leadeth me -- Revive us again -- For the beauty of the earth -- My Jesus, I love Thee -- Shall we gather at the river? -- Day by day -- Jesus paid it all -- Now the day is over -- Onward Christian soldiers -- Rejoice ye pure in heart -- Safe in the arms of Jesus -- O little town of Bethlehem -- The king of love my Shepherd is -- The ninety and nine -- Sweet by and by -- Rescue the perishing -- Jesus loves even me -- I need Thee every hour -- Lord, speak to me -- Blessed assurance -- It is well with my soul -- Another year is dawning -- Bringing in the sheaves -- Take my life and let it be -- I will sing of my Redeemer -- All the way my Savior leads me -- O the deep, deep love of Jesus -- Jesus, I am resting, resting -- Like a river glorious -- O Master, let me walk with Thee -- God be with you -- O love that wilt not let me go -- Take time to be holy -- 'Tis so sweet to trust in Jesus -- How great Thou art -- Standing on the promises -- WHen they ring the golden bells -- Leaning on the everlasting arms -- Trust and obey -- Sunshine in my soul -- Yesterday, today, forever -- My faith has found a resting place -- America the beautiful -- When the roll is called up yonder -- I must tell Jesus -- At Calvary -- Jesus loves the little children -- I surrender all -- Under His wings -- Count your blessings -- Face to face -- When we all get to heaven -- There is power in the blood -- O that will be glory -- Does Jesus care? -- This is my Father's world -- Near to the heart of God -- God will take care of you -- His eye is on the sparrow -- Have Thine own way, Lord -- Joyful, joyful, we adore Thee -- He keeps me singing -- Our Great Savior -- In the garden -- Brighten the corner where you are -- The old rugged cross -- The love of God -- Wonderful grace of Jesus -- I'd rather have Jesus -- Great is Thy faithfulness -- Little is much when God is in it -- Precious Lord, take my hand -- He lives -- Beyond the sunset -- Search me, O God -- It is no secret -- His name is wonderful -- The all sufficient King. God -- Now thank we all our God -- The Lord's my Shepherd -- Doxology -- Praise God, from whom all blessings flow -- Sing praise to God who reigns above -- Fairest Lord Jesus -- Praise ye the Lord, the Almighty -- Behold the Savior of mankind -- Behold the glories of the Lamb -- Alas! and did my Savior bleed -- I sing the mighty power of God -- Jesus shall reign -- O God, our help in ages past -- God is the refuge of His saints -- Am I a soldier of the cross? -- An can it be that I should gain? -- O for a thousand tongues to sing -- Hark! The herald angels sing -- Christ the Lord is risen today -- Jesus, lover of my soul -- Hallelujah chorus (from The Messiah) -- Messiah (Handel) -- O come, all ye faithful -- When morning gilds the skies -- Guide me, O Thou great Jehovah -- O happy day, that fixed my choice -- Come, Thou fount of every blessing -- Father, whate'er of earthly bliss -- There is a fountain -- O for a closer walk with God -- God moves in a mysterious way -- Rock of ages -- All hail the power of Jesus' name -- Amazing grace -- Though troubles assail us -- How firm a foundation -- There is a balm in Gilead -- Praise the Savior, ye who know Him! -- The Star-Spangled Banner -- Angels from the realms of glory -- Silent night -- Jesus, I my cross have taken -- In the cross of Christ I glory -- Holy, holy, holy! Lord God Almighty -- My faith looks up to Thee -- Of for a faith that will not shrink -- My country, 'Tis of Thee -- Lead, kindly light -- O worship the King -- The solid rock -- Just as I am -- Nearer, my God, to Thee -- I heard the voice of Jesus say -- Abide with me -- It came upon the midnight clear -- In heavenly love abiding -- Crown Him with many crowns -- Good King Wenceslas -- Still, still with Thee -- What a friend we have in Jesus -- More love to Thee, O Christ -- Stand up, stand up for Jesus -- Eternal Father, strong to save -- Jesus loves me -- I gave my life for thee -- Battle hymn of the republic -- He leadeth me -- Revive us again -- For the beauty of the earth -- My Jesus, I love Thee -- Shall we gather at the river? -- Day by day -- Jesus paid it all -- Now the day is over -- Onward Christian soldiers -- Rejoice ye pure in heart -- Safe in the arms of Jesus -- O little town of Bethlehem -- The king of love my Shepherd is -- The ninety and nine -- Sweet by and by -- Rescue the perishing -- Jesus loves even me -- I need Thee every hour -- Lord, speak to me -- Blessed assurance -- It is well with my soul -- Another year is dawning -- Bringing in the sheaves -- Take my life and let it be -- I will sing of my Redeemer -- All the way my Savior leads me -- O the deep, deep love of Jesus -- Jesus, I am resting, resting -- Like a river glorious -- O Master, let me walk with Thee -- God be with you -- O love that wilt not let me go -- Take time to be holy -- 'Tis so sweet to trust in Jesus -- How great Thou art -- Standing on the promises -- WHen they ring the golden bells -- Leaning on the everlasting arms -- Trust and obey -- Sunshine in my soul -- Yesterday, today, forever -- My faith has found a resting place -- America the beautiful -- When the roll is called up yonder -- I must tell Jesus -- At Calvary -- Jesus loves the little children -- I surrender all -- Under His wings -- Count your blessings -- Face to face -- When we all get to heaven -- There is power in the blood -- O that will be glory -- Does Jesus care? -- This is my Father's world -- Near to the heart of God -- God will take care of you -- His eye is on the sparrow -- Have Thine own way, Lord -- Joyful, joyful, we adore Thee -- He keeps me singing -- Our Great Savior -- In the garden -- Brighten the corner where you are -- The old rugged cross -- The love of God -- Wonderful grace of Jesus -- I'd
"150 of the world's greatest hymn stories"--Cover.
Includes bibliographical references and indexes.
Keywords: Hymns -- History and criticism